Modyfikacja stylu relacyjnego i strategii rozwiązywania sytuacji trudnych w obszarze zawodowym - komunikat z badań = Modification of the relational styles and strategies of dealing with difficult situations in the professional area - Doliński, Artur (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the original concept of relational styles and strategies of dealing with difficult situations in professional area. The research was carried out in a group of middle and senior managers of one of the large corporations in Poland. The relational styles represented by the managers were diagnosed as well as their perception of difficult situations in the professional activity.
Keywords: styl relacyjny; sytuacja trudna; modyfikacja wzorów zachowań; model reagowania na agresję; model reagowania na presję; modele korygowania zachowań; relational style; difficult situation; modification of behavior patterns; model of response to aggression; model of response to pressure; models of behavior correction